Antioxidant Properties and Fatty Acid Profile of Cretan Extra Virgin Bioolive Oils: A Pilot Study - Dariusz Nowak; Michał Gośliński; Cezary Popławski (International Journal of Food Science)
Olive oil is considered a valuable ingredient of human diet. It is a good source of mono- and polyunsaturated fatty acids, as well as other bioactive compounds, especially polyphenols. The composition of olive oil depends mainly on the variety of plant, cultivation practices, and manufacturing conditions. Traditional processing methods may ensure better quality and health benefits. Therefore, the aim of the study was the evaluation of antioxidant properties and fatty acid profile of Cretan extra virgin bioolive oils. These ones were compared with commercial Spanish, Italian, and Greek extra virgin olive oils. Obtained results showed that sample Cretan 1 had about 15% higher antioxidant capacity and about 60% higher total polyphenol content than commercial counterparts. This one had also a favorable profile of fatty acids, especially 20% more linoleic acid. We concluded that traditional production methods, using millstones, cold pressing, and without centrifugation and filtration ensure better olive oil quality and related health benefits.